DONALD TRUMP’S POLICY AGAINST NORTH KOREA’S BALLISTIC NUCLEAR WEAPON TEST - Agung Prija Utama; Chandra Purnama; Wawan Budi Darmawan (JWP (Jurnal Wacana Politik), 2022)
This study aims to identify the typology of the United States foreign policy towards North Korea’s ballistic nuclear weapons test during the Donald Trump administration. The typology of foreign policy will be explained by using James N. Rosenau’s adaptive foreign policy model which refers to two factors that influence it, namely external and internal changes in the United States environment which are influenced by three classifications, namely personal change, political change, and social-economic change against each factor, both externaly and internaly. This research is a descriptive qualitative research. The data collection method used in this research is literature study. The data were obtained from various books, journals, electronic media and digital documents/reports, while the data analysis used sorting from the various data that had been collected and analyzing the data that was close to the focus in this study. Interpretation of the data obtained can then be poured through a description in form of writing and graphics. Based on the research that has been done, it was found that the typology of US foreign policy adaptation is promotive adaptation.